A Quasi-Optimal Clustering Algorithm for MIMO-NOMA Downlink Systems - Saggese, Fabio; Moretti, Marco; Abrardo, Andrea (IEEE wireless communications letters, 2020)
In this letter we consider a resource allocation problem for multi-user MIMO non orthogonal multiple access (MU-MIMO-NOMA) downlink transmissions. Under the NOMA paradigm, users are organized in clusters of strong/weak pair and our aim is to find an optimal clustering, beamforming and power allocation scheme to minimize the power transmitted subject to a rate constraint for each user. Since the joint optimization problem is intractable, we split it in three sub-problems: clustering, which is formulated as a mixed integer linear programming (MILP) problem, beamforming and power allocation. Simulations results show that the our proposed scheme greatly outperforms both the classical OMA scheme and state-of-the-art NOMA techniques.